Metal anodes meet ionic liquids: An interfacial perspective - Jamil, Rabia; Loomba, S.; Kar, M.; Collis, G.E.; Silvester-Dean, Debbie; Mahmood, N. (2024)
Ionic liquids (ILs) are nonvolatile, intrinsically conductive electrolytes with high thermal and electrochemical stability. They represent a fascinating yet-to-be-fully exploited electrolyte class that could be appropriate for metal anode batteries. Through their chemical design and structure modification, ILs are highly tunable electrolytes. Exploring the impact of their different structures on the anode/electrolyte interface allows the tailoring of ILs for post-Li-ion batteries. This comprehensive review gives an overview of the current challenges of different metal anodes, followed by a fundamental understanding of metal anode/electrolyte interface evolution in ILs in a coherent manner, highlighting the potential of ILs to address the specific problems of each type of metal anode. Electrochemical reactions—such as passivating film formation, metal deposition/stripping, dendritic growth—occurring at the metal anodes in IL-based electrolytes are openly debated, and how ILs can help to improve these phenomena is presented. Unanswered scientific questions on the nature of electrode/electrolyte coupling are identified. Finally, conclusions and perspectives are proposed regarding the development, limitations, and opportunities of metal anode/ionic liquid interfaces. This timely review will expose literature gaps and provide novel opportunities to exploit ILs in materials science and technology research.